EFFECT OF FEEDING FORMALDEHYDE TREATED BARLEY ON PRODUCING COLOSTRUM AND MILK AND THEIR COMPENONTS AND SOME BLOOD PARAMETERS IN DAMASCUS GOATS - Omar ALMallah; M. N Abdullah,; , N.Y Abbo; G. K Khattab (Mesopotamia Journal of Agriculture)
This study was conducted in Al-Rashidiya animal breeding station, by using 16 (3-5 years old) of Damascus – Cyprus female goats in the last two months of pregnancy with average body weight 61.25 kg. Goats were divided according to their body weight and milk production during the previous season into two groups, the first was fed on ration contained untreated barley (UTB), while the second group fed on ration contained barley treated with acidic- formaldehyde solution (FTB). both groups were approximately born in the same expected period. Daily feed intake was restricted with 1.25 kg /goat through the experimental period. Results was indicated that feeding FTB led to non-significant improved in colostrums yield 135 g/ hr as compared UTB 109 g/ hr., but the protein 3.88 % and lactose 5.55% increased significantly (p<0.05) as compared with UTB 3.49 and 5.15 respectively. Also , it was noted a significant (p<0.05) increase in milk yield 1185 g/day and its content of fat 5.20%, total solid 8.94% and energy 841kcal/kg in FTB as compared with 959 g milk per day , total solid 8.68 % and energy 728 kcal/ kg in UTB group. Although, the significant (p<0.05) increased in birth weight 4.58 kg in the group that fed on FTB as compared with 3.29 kg for group fed on UTB, but average daily gain was not differ among treatments. Lowered barley degradability caused a significant (p<0.05) decreased blood total protein 5.98 g/dl as compared UTB group 7.03 g/ dl.